Comparative study about the powers and the representativeness of employee representatives in French and German enterprises - Panu Poutvaara; Till Nikolka; Daniel Leithold; Katrin Oesingmann; Daniela Wech (ifo Institut - Leibniz-Institut für Wirtschaftsforschung an der Universität München, 2017)
The first part of the study compares the institutional settings of employee representation and collective bargaining in France and Germany. One important difference is that in France, many aspects of collective agreements are defined by labour law, whereas in Germany, collective bargaining partners are given far greater scope for negotiation. The second part of the study analyses the economic effects of different institutional settings. Greater wage flexibility has positive effects on competitiveness and employment. In the last part of the study, reform proposals made by Jean-Denis Combrexelle, President of the Department of Social Affairs of the government council, are evaluated. His proposals to enlarge the scope of collective bargaining and also allow firm-level bargaining are judged positively. Moving from the indeterminate duration of firm agreements to well-defined contract periods would reduce uncertainty for both firms and workers. The implementation of these reform proposals would be most effective if they were combined with a peace obligation, meaning that no strikes would be allowed for an agreed period of time. The proposal to maintain extensions of industrial agreements by the Labour Minister is counterproductive and would partly eliminate gains from other proposals.
Keywords: K31; J51; J52; J53; 330